Printing service on the go - Nurul Husna Tasnim, Mohamad Zamri (2018)
Printing Service on the Go is a mobile application that is aimed for UMP student which purposes to help student find a place to print the assignments. The problems that are faced by UMP students regarding to this project are unaware the amount of the printing service shop available around UMP, insufficient time to find a place to print and have to spend most of the time just to line up in printing shop in UMP to print the assignment/s. The goal of this project is to develop a printing service on the go that is specific for UMP students. Rapid Application Development (RAD) is the methodology used for this project. Overall, this mobile application could solve the problem among UMP student to print the assignments.